De novo loss- or gain-of-function mutations in KCNA2 cause epileptic encephalopathy - Syrbe, Steffen; Hedrich, Ulrike B S; Riesch, Erik; Djémié, Tania; Müller, Stephan; Møller, Rikke S; Maher, Bridget; Hernandez-Hernandez, Laura; Synofzik, Matthis; Caglayan, Hande S; Arslan, Mutluay; Serratosa, José M; et al. (Nature genetics, 2015)
Epileptic encephalopathies are a phenotypically and genetically heterogeneous group of severe epilepsies accompanied by intellectual disability and other neurodevelopmental features. Using next-generation sequencing, we identified four different de novo mutations in KCNA2, encoding the potassium channel KV1.2, in six isolated patients with epileptic encephalopathy (one mutation recurred three times independently). Four individuals presented with febrile and multiple afebrile, often focal seizure types, multifocal epileptiform discharges strongly activated by sleep, mild to moderate intellectual disability, delayed speech development and sometimes ataxia. Functional studies of the two mutations associated with this phenotype showed almost complete loss of function with a dominant-negative effect. Two further individuals presented with a different and more severe epileptic encephalopathy phenotype. They carried mutations inducing a drastic gain-of-function effect leading to permanently open channels. These results establish KCNA2 as a new gene involved in human neurodevelopmental disorders through two different mechanisms, predicting either hyperexcitability or electrical silencing of KV1.2-expressing neurons.
Keywords: mutace; dospělí; Epilepsy; Female; Infant; předškolní dítě; dítě; Pedigree; Adult; mladý dospělý; ženské pohlaví; sekvence aminokyselin; rodokmen; lidé; draslíkový kanál Kv1.2; křeče u dětí; Kv1.2 Potassium Channel; Mutation; genetická predispozice k nemoci; Amino Acid Sequence; Genetic Predisposition to Disease; kohortové studie; Cohort Studies; epilepsie; Male; kojenec; Child, Preschool; Young Adult; Child; mužské pohlaví; Spasms, Infantile; Humans